2021
DOI: 10.1111/1541-4337.12798
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae biomass as a source of next‐generation food preservatives: Evaluating potential proteins as a source of antimicrobial peptides

Abstract: Saccharomyces cerevisiae is the main biotechnological tool for the production of Baker's or Brewer's biomasses, largely applied in beverage and fermentedfood production. Through its gene expression reprogramming and production of compounds that inactivate the growth of other microorganisms, S. cerevisiae is able to grow in adverse environments and in complex microbial consortia, as in fruit pulps and root flour fermentations. The distinct set of up-regulated genes throughout yeast biomass propagation includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 139 publications
(257 reference statements)
0
23
0
1
Order By: Relevance
“…Other studies have reported in vitro and in vivo S. cerevisiae peptide health-promoting activities, including those attributed to brewer's yeast or baker's yeast, as mentioned previously [7]. Two saccharomycins, VSWYDNEYGYSTR and ISWYDNEYGYSAR, encrypted in glyceraldehyde-3-phosphate dehydrogenase (GAPDH) that converts glyceraldehyde-3phosphate to 1, 3 bis-phosphoglycerate in the glycolytic pathway, encoded by the TDH gene (isoforms 1, 2, or 3), have been reported and characterized as a killer-like toxin naturally secreted by S. cerevisiae, with the former detected in the FLPC fractions, especially Fraction 4 (Table S2) [29][30][31][32].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Other studies have reported in vitro and in vivo S. cerevisiae peptide health-promoting activities, including those attributed to brewer's yeast or baker's yeast, as mentioned previously [7]. Two saccharomycins, VSWYDNEYGYSTR and ISWYDNEYGYSAR, encrypted in glyceraldehyde-3-phosphate dehydrogenase (GAPDH) that converts glyceraldehyde-3phosphate to 1, 3 bis-phosphoglycerate in the glycolytic pathway, encoded by the TDH gene (isoforms 1, 2, or 3), have been reported and characterized as a killer-like toxin naturally secreted by S. cerevisiae, with the former detected in the FLPC fractions, especially Fraction 4 (Table S2) [29][30][31][32].…”
Section: Discussionmentioning
confidence: 53%
“…Besides its GRAS status, low-fat and low-sodium contents, and its ability to transform food matrices for human consumption, S. cerevisiae also provides nutritional and health-promoting compounds, such as amino acids, β-glucans and mannans, lipids, B-complex vitamins, minerals, and oligopeptides, which contribute to the management of diabetic foot ulcers by controlling fungal infections and wound healing, cholesterol levels, allergic symptoms, and microorganism growth [2,3,[19][20][21][22][23][24]. Spent brewer yeast or baker's yeast extracts, rich in oligopeptides, are widely marketed for dietary supplementation purposes, and their biological properties are explored to confirm the claimed bio-functionalities, such as antioxidant, antihypertensive, antimicrobial, alphaglucosidase inhibitor, anti-lipolysis, anti-diabetes, mitogenic, immunomodulatory, and anti-obesity properties [2,7,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Saccharomyces cerevisiae, a yeast widely used in food and beverage production, was observed to provide a valuable source of different nutrients, the most important being the bioactive peptides which can become a major supporter in pharmaceutical therapies [1]. In this paper, the main aim was to predict in silico the health effects of bioactive peptides sourced from spent brewery yeast proteins, with a focus on their antihypertensive and antioxidant effects.…”
mentioning
confidence: 99%